Hindu residents' satisfaction with spatial layouts in low-cost flats, Selangor, Malaysia - Ooi, Siew Choong (Richard) (2015)
Religious and cultural considerations of specific communities are usually overlooked in the design of low-cost flats in Malaysia. This is probably due to limitations on the construction budget as well as poor understanding of religio-cultural needs. The result is a spatial layout that is generic and purely functional, in which Hindu households will be experiencing some degree of dissatisfaction. Furthermore, they were built primarily to relocate squatters from private or government land. The consequences of residential dissatisfaction include emotional and psychological stress. The aim of this study is to observe the degree of Hindu residents’ satisfaction with the spatial layout of LCFs in Selangor. The methodology employed to determine the level of satisfaction is a combination of 150 surveys and 5 physical observations, supported by 30 interviews,of low-cost flat case studies conducted around Puchong in Selangor. The data is examined via a combination of discourse, statistic and spatial studies. The results indicate that Hindu residents are generally satisfied with the spatial layouts of their low-cost flats with some reservations. A common complaint is that some rooms are spatially and functionally inadequate for their intended religio-cultural purposes. It appears that many Indian households rely more on cosmological and metaphysical sources, rather than the physical and material, for comfort and well-being. Nevertheless,design strategies, such as the addition of spaces for altars, may enhance the living standard of Hindu families.